Survival abdominal gunshot injury: a rare case - Gajbhiye, Ashok S.; Deshmukh, M. N.; Jaipuriya, Parag; Jaipuriya, Parag; Mehata, P.; Kumar, Abhinav; Kumar, Abhinav (International Surgery Journal, 2018)
A 55 years old male patient came to the casualty of a medical college and hospital with alleged history of assault with firearm injury on his back. Patient was conscious with GCS 15/15, his pulse rate was 133 beats per min, blood pressure was 100/60 mmHg, SpO2 was 95% and pallor was present. On local examination there was single entry wound at lower back on left side of size 1 cm X 1 cm with no exit wound. Generalized abdominal tenderness and guarding was present. Patient was immediately resuscitated. Blood grouping, cross match were sent immediately. Abdominal radiograph did not show any gas under the diaphragm but a foreign body (a bullet) was seen. Ultrasonography and computerized tomography scan of the abdomen was suggestive of hemoperitonium and a foreign body bullet in abdomen. Exploratory laparotomy showed moderate hemoperitonium of about 1000 ml which was sucked out completely. Evidence of retroperitoneal rent of size approximately 1 cm X 1 cm seen with oozing through it which was closed in layers. A bullet was seen in the anterior abdominal wall but skin was intact. Five jejunal perforations distal to 20 cm from the duodenojejunal flexure were seen and the bullet was removed from the anterior abdominal wall. Resection of the jejunal segment with jejuno-jejunal anastomosis was done. Jejunal mesenteric rents were closed. Abdominal wall closed in layers. Post-operative recovery was uneventful. Patient was discharged on the 10th post-operative day. Early diagnosis and treatment in the golden hours can save the life of the patients. A mass education on the dangers of these guns and the harm they can cause as well as legal regulations for their restricted use seem to be necessary.